An Unusual Femoral Sheath Severing with Successful Recapture: A Case Report - Runjić, Frane; Matetic, Andrija; Bunc, Matjaž; Crnčević, Nikola; Kristić, Ivica (Reports (MDPI), 2021)
This study presents a case of a successful severed femoral sheath recapture during transfemoral transcatheter aortic valve replacement (TAVR). During skin tunneling with a scalpel, the discontinuity of the femoral sheath occurred. Grasping of the distal sheath with the surgical hemostat was attempted unsuccessfully. A proximal part of the severed sheath was removed and Medtronic Sentrant introducer sheath (14 French) was then placed over the existing Confida wire which permanently remained in position, followed by the introduction of the Amplatz Left 2 (AL2) catheter which pushed the severed sheath in the ascending aorta over the Confida wire. The crucial maneuver was the entanglement of the severed sheath in the aortic non-coronary cusp which allowed for its entrapment by the AL2 catheter. This allowed for the coronary guidewire BMW Universal (0.014″) placement and a slow balloon retrieval (SeQuent NEO 2.5 × 25 mm2) of the severed sheath into the introducer sheath. The guidewire/balloon catheter was then exchanged for the support wire (0.035″) followed by the removal of the introducer sheath, AL2 catheter and the severed sheath. In conclusion, sheath severing is a complex accidental event during TAVR, which can be solved by intra-aortic recapture and retraction.